Modeling of potential field data for detecting structural and tectonic framework of Esh El Mellaha area, Red Sea, Egypt - Abdelbaset M. Abudeif; Zakaria Hamimi; Gaber M. Gaber; Adel Kotb; Nasir Alarifi; Stefano Bellucci; Marwa M. Masoud (Scientific Reports)
Abstract The main objective of this research is to get a comprehensive view on the subsurface geological data on the Esh El Mellaha area and environs, Red Sea, Egypt. This includes determining the depth and structural characteristics of the basement surface beneath the region, as well as identifying additional gravity and magnetic sources and potential structures within the sedimentary cover. To achieve this goal, Bouguer gravity and aeromagnetic data were used, processed and analyzed. Various depth estimation techniques were employed to analyze subsurface structures, each offering distinct advantages. Euler Deconvolution effectively delineates structural discontinuities and fault systems, while the Source Parameter Imaging (SPI) method improves depth accuracy through wavenumber analysis. The Analytical Signal method enhances resolution, providing detailed depth variations. Across these methods, the estimated depth ranges from 300 to 5000 m, with an average depth of approximately 2380 m, offering critical insights into the subsurface geological framework. Two-dimensional (2.5D) modeling was conducted on two selected gravity and magnetic profiles to estimate the depth, dip, density, and magnetic susceptibility of the source bodies. Additionally, three-dimensional (3D) modeling was applied to Bouguer gravity and Reduced-to-the-Pole (RTP) magnetic profiles, providing a detailed representation of the causative source structures. The results of the 3D inversion of gravity and magnetic data reveal the subsurface distribution of density and magnetic susceptibility, aiding in the identification of major geological structures. The sectional maps and 3D models illustrate the vertical and horizontal variations in subsurface formations, highlighting distinct anomaly zones that may correspond to faults and lithological changes. The obtained results indicate that the sedimentary succession thickness is ranging from 1.0 to 2.2 km, a finding corroborated by the borehole data. Positive structural features identified in these models suggest promising targets for potential hydrocarbon reservoirs.